Structure-Based Evolution of Low Nanomolar O‑GlcNAc Transferase Inhibitors - Martin, Sara E. S; Tan, Zhi-Wei; Itkonen, Harri M; Duveau, Damien Y; Paulo, Joao A; Janetzko, John; Boutz, Paul L; Törk, Lisa; Moss, Frederick A; Thomas, Craig J; Gygi, Steven P; Lazarus, Michael B; et al. (Journal of the American Chemical Society, 2018)
Reversible glycosylation of nuclear and cytoplasmic proteins is an important regulatory mechanism across metazoans. One enzyme, O-linked N-acetylglucosamine transferase (OGT), is responsible for all nucleocytoplasmic glycosylation and there is a well-known need for potent, cell-permeable inhibitors to interrogate OGT function. Here we report the structure-based evolution of OGT inhibitors culminating in compounds with low nanomolar inhibitory potency and on-target cellular activity. In addition to disclosing useful OGT inhibitors, the structures we report provide insight into how to inhibit glycosyltransferases, a family of enzymes that has been notoriously refractory to inhibitor development.